Smart and energy aware routing for the internet of mobile things - Beh, Zi Xuan (2021)
This project is to design a smart and energy aware routing algorithm for the Internet of Mobile Things. Reason of doing this project is because the discovery of problem such as high occurrence in routing loop and unsuccessful packet routing under high mobility environment for Internet of Mobile Things. Therefore, a smart and energy efficient routing algorithm is necessary to be developed and the level of energy consumption is important to be improved and observed. In this project, we aim to design and develop a new routing algorithm entitled “SEA routing protocol” that is believed to resolve the problems mentioned which will lead to high energy consumption in IoMT devices. The network simulation process is run in the CupCarbon software which is known as a smart city & IoT wireless sensor network simulator. The routing algorithm are developed and coded in Sen Script. In this project, the routing algorithm can perform disqualify node detection and energy aware routing. To summarize, to solve the problem of high occurrence in routing loop and unsuccessful packet routing, two functions are designed and performed. First function will be to filter out the disqualify node in the network based on their respective battery capacity. Second, four different are generated based on the scenario detected. Hence, two scripts written in SenScript will be generated where one is call routing.csc and battery.csc files. Both version of scripts will be simulated and generate an energy consumption report. At the end of the project, packet delivery ratio and energy consumption report are generated which are the key elements to prove the SEA routing algorithm is smart and energy aware. Based on results obtained, the energy consumption level consumed by the network is 0.05 joule to 0.04 joule. Result also shows that when delay instruction is applied before routing message is generated can contributes in the energy efficient context. This can also be concluded that the SEA routing algorithm is smart and energy aware based on the results obtained.